Electroconvulsive therapy use in the adult U.S. correctional setting: A case report and literature review. Issue 3 (4th January 2021) - Martin, Mark; Ureste, Peter
Abstract: Mr. C is a 45‐year‐old male inmate who was found in his cell unresponsive and mute. He had poor food and fluid intake for the last four days and was later found standing in place, frozen, and resistant to movement when encouraged by a corrections officer to rest in his bed. His symptoms were consistent with catatonia, a severe motor syndrome that can be life‐threatening. The patient had a psychiatric history of bipolar I disorder with multiple past episodes of catatonia. Lorazepam was ineffective at reversing his catatonic symptoms, and his serum creatinine kinase level eventually began to rise, suggestive of muscle breakdown and worsening severity. The treating psychiatrist wanted access to electroconvulsive therapy (ECT) to treat Mr. C's catatonia but encountered numerous legal and logistical barriers which made this treatment option unavailable. The article reviews the scant literature on ECT use in the adult U.S. correctional system, identifies barriers, and discusses a recommended ECT referral process for inmates.